Modern Approach to Diagnosis and Treatment of Bladder Cancer - Ziglioli, Francesco; Maestroni, Umberto (IntechOpen, 2021)
Bladder cancer is an important topic in the field of urology affecting human overall health and well-being. There have been many advancements in the diagnosis and treatment of bladder cancer, one of the most common carcinomas seen in urology. As such, it is of the utmost importance for urologists and oncologists to have comprehensive and proper knowledge of the disease's diagnostic pathways as well options for its treatment. This book presents the state of the art in diagnosing and treating bladder cancer, including the latest findings on molecular classification of this tumor, chemotherapy, immunotherapy, and minimally invasive techniques for surgical treatment.